2015
DOI: 10.1002/jcb.25194
|View full text |Cite
|
Sign up to set email alerts
|

Urocortin Attenuates TGFβ1‐Induced Snail1 and Slug Expressions: Inhibitory Role of Smad7 in Smad2/3 Signaling in Breast Cancer Cells

Abstract: Corticortropin-releasing hormone (CRH) family are multifunctional endocrine-factors that regulate proliferation, apoptosis, and migration of various types of cancer cells. Deregulation of the transforming growth factor β1(TGFβ1) signal transduction promotes aggressive metastatic properties in late-stage breast cancers. We previously have demonstrated in breast cancer cell line that CRH suppressed TGFβ1-induced Epithelial-Mesenchymal Transition (EMT) via induction of E-cadherin. Our present data in MCF-7 and MD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
2
7
0
Order By: Relevance
“…Moreover, it was found that SMAD7 is markedly correlated with SMAD-2 as shown in Fig. 5B, which is also consistent with the finding that the expression of SMAD-2 is regulated by inhibitory SMAD-7 activity in a negative feedback in cancer cells (73).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, it was found that SMAD7 is markedly correlated with SMAD-2 as shown in Fig. 5B, which is also consistent with the finding that the expression of SMAD-2 is regulated by inhibitory SMAD-7 activity in a negative feedback in cancer cells (73).…”
Section: Discussionsupporting
confidence: 90%
“…This clearly indicates that SMAD7 can mimic the effect of RAC1B on transcriptional induction of individual genes involved in EMT and cell invasion. In good match with our results, siRNA-mediated knockdown of SMAD7 increased TGFβ-induced activation of SMAD3 in MDA-MB-231 cells [ 31 ]. In sum, these data show that SMAD7 mimics the inhibitory effect of RAC1B on ALK5 protein expression and provide further evidence for the assumption that RAC1B exerts its inhibitory effect on TGFβ/Smad-mediated gene expression at least in part through upregulation of SMAD7.…”
Section: Resultssupporting
confidence: 91%
“…Increasing reports indicate that a complex cross-talk exists between the β-catenin pathway and other signaling molecules, and EMT-corresponding effectors 2224. In the present study, we identified the in vitro effect of β-catenin on different malignant phenotypes in U87 glioblastoma cells.…”
Section: Discussionmentioning
confidence: 79%